Determinants of continuous mobile banking usage in Malaysian police force - Tulasi, Martin (2022)
Mobile banking has the potential to improve both people's lives and bank efficiency. The long-term success of mobile banking is dependent on its consistent use. This study aims to investigate determinants of continuous mobile banking usage in the Malaysian police force. Police officers are one of the essential services among government servants in Malaysia. Work patterns and internal work time challenges among police officers. Mobile banking services allow police officers to conduct banking transactions without going to the bank. The main elements influencing police officers' continuous usage intention of mobile banking services are technology acceptance, quality dimension, and protection motivation. Underpinned by the Unified Theory of Acceptance and Use of Technology (UTAUT), Delone Mclean IS model and Protection Motivation Theory. The partial least squares technique was used to analyse empirical data from 562 Malaysian police officers who had prior experience with mobile banking. Results show a positive relationship between technology acceptance, perceived service quality, perceived system quality positively affect continuous usage intention. Hence, perceived information quality and protection motivation do not have significant effects on continuous usage Intention. Technology acceptance and protection motivation positively have significant effects on continuous usage behaviour. Moreover, continuous usage intention positively significant effects mediate the relationship between technology acceptance and continuous usage behaviour. Instead, continuous usage intention positively not significant effects mediates the relationship between protection motivation and continuous usage behaviour. In addition, mobile banking usage intention positively affects continuous usage behaviour. As a result, banks should prioritise these factors in their decision-making to increase the perceived benefits of mobile banking.